2012
DOI: 10.1177/2045125312470130
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic cognitive effects of levodopa and dopamine agonists on patients with Parkinson’s disease: a review

Abstract: Abstract:The spatiotemporal progression of dopamine depletion in Parkinson's disease (PD) provides a special model for assessing dopaminergic effects on neural systems with differential baseline dopamine levels. This study aims at reviewing cognitive effects of dopaminergic stimulation in PD. While considering dopaminergic drugs (levodopa or dopamine agonists), temporal intervals (acute or chronic) and cognitive domains, we found that empirical evidence was almost focused on acute effects of levodopa on execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 90 publications
(202 reference statements)
4
61
1
1
Order By: Relevance
“…Finally, all of our subjects were in the ON medication state during the study period, making it difficult to determine the medication effects on cognition and brain volume. Although cognitive deficits in PD could be a result of dopaminergic treatment (Dopamine Overdose Hypothesis) or due to dopaminergic deficiency (Dopamine Depletion Hypothesis) [31], thus far, there is a lack of sufficient evidence to conclude the effects of medication on cognition in PD [32]. Also, while previous studies have shown improved functional connectivity when PD patients were in the ON medication state (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, all of our subjects were in the ON medication state during the study period, making it difficult to determine the medication effects on cognition and brain volume. Although cognitive deficits in PD could be a result of dopaminergic treatment (Dopamine Overdose Hypothesis) or due to dopaminergic deficiency (Dopamine Depletion Hypothesis) [31], thus far, there is a lack of sufficient evidence to conclude the effects of medication on cognition in PD [32]. Also, while previous studies have shown improved functional connectivity when PD patients were in the ON medication state (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…These alterations lead to a progressive loss of dopaminergic neurons and the clinical signs of illness [63][64][65][66][67][68]. However, these pathologic changes are not limited to the substantia nigra pars compacta.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…The aberrant regulation of neurotransmitters has been implicated in numerous disease states including schizophrenia, Parkinson's disease, Alzheimer's disease, mood disorders, attention-deficit/hyperactivity disorder (ADHD), and drug addiction (Brambilla et al, 2003;Moghaddam and Javitt, 2012;Lesch et al, 2013;Paula-Lima et al, 2013;Poletti and Bonuccelli, 2013;Quintero, 2013). Of particular note, the frontal cortex is a glutamate-rich brain region and deficits in this area cause poor impulse control, distractibility, hyperactivity, forgetfulness and poor organization and planning (Stuss and Levine, 2002).The frontal cortex is organized into different cortical layers, including the cingulate cortex, prelimbic cortex, infralimbic cortex, and the dorsal peduncle.…”
Section: Introductionmentioning
confidence: 99%